2008
DOI: 10.1038/mt.2008.118
|View full text |Cite
|
Sign up to set email alerts
|

Stable and Functional Lymphoid Reconstitution in Artemis-deficient Mice Following Lentiviral Artemis Gene Transfer Into Hematopoietic Stem Cells

Abstract: Patients with mutations in the Artemis gene display a complete absence of T- and B lymphocytes, together with increased cellular radiosensitivity; this leads to a radiosensitive severe combined immunodeficiency (RS-SCID). Allogenic hematopoietic stem-cell (HSC) transplantation is only partially successful in the absence of an human leukocyte antigen-genoidentical donor, and this has prompted a search for alternative therapeutic approaches such as gene therapy. In this study, a self-inactivated lentiviral vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 33 publications
3
50
0
Order By: Relevance
“…16 We subsequently demonstrated that overexpression of Artemis after lentiviral transduction is associated with cytotoxicity, a halt in cell cycle progression, and fragmentation of genomic DNA ultimately resulting in apoptosis. 18 These results, along with the previous reports demonstrating incomplete immune reconstitution of SCID-A after ex vivo transduction with an exogenous promoter, 16,17 emphasize the importance of providing Artemis expression at a level that is nontoxic and yet sufficient to correct the SCID-A T -B -phenotype. Accordingly, we isolated and characterized the human Artemis promoter (APro) as a sequence extending 1 kilobase upstream from the human Artemis translational start site on human chromosome 10.…”
Section: Introductionmentioning
confidence: 51%
See 2 more Smart Citations
“…16 We subsequently demonstrated that overexpression of Artemis after lentiviral transduction is associated with cytotoxicity, a halt in cell cycle progression, and fragmentation of genomic DNA ultimately resulting in apoptosis. 18 These results, along with the previous reports demonstrating incomplete immune reconstitution of SCID-A after ex vivo transduction with an exogenous promoter, 16,17 emphasize the importance of providing Artemis expression at a level that is nontoxic and yet sufficient to correct the SCID-A T -B -phenotype. Accordingly, we isolated and characterized the human Artemis promoter (APro) as a sequence extending 1 kilobase upstream from the human Artemis translational start site on human chromosome 10.…”
Section: Introductionmentioning
confidence: 51%
“…Two independent groups reported the correction of murine models of SCID-A by transplantation of genetically modified HSCs. 16,17 In both studies, Artemis-deficient animals were transplanted with HSCs that had been transduced with a lentiviral vector encoding human Artemis regulated by the human phosphoglycerate kinase (PGK) promoter, resulting in reconstitution of B and T lymphocyte compartments. 16,17 Surprisingly, Mostoslavsky and colleagues reported lack of lymphoid reconstitution in RAG-1-deficient animals transplanted with SCID-A HSCs that had been transduced using lentiviral vectors encoding human Artemis regulated by the stronger cytomegalovirus (CMV) or elongation factor-1a (EF1a) promoter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grafting of lentivirally transduced HSCs into irradiated Artemis-knockout mice lead to effective T-cell reconstitution, and although in a second study 1/13 mice did develop a thymoma, this was not thought to be vector related because the recipient strain is known to be tumour prone. 17 A canine model of leukocyte adhesion deficiency, another rare neutrophil disorder characterized by serious bacterial and fungal infections, was successfully ameliorated using Foamy Virus vectors expressing the b-integrin CD18. 18 Again, preconditioning of animals using non-myeloablative conditioning was essential and relatively modest levels of gene modified cell engraftment was sufficient for the sustained resolution of symptoms.…”
Section: Gene Therapy For Wiskott-aldrich Syndrome Gets Underwaymentioning
confidence: 99%
“…Most investigators in the field have moved to such vectors, either in a γ-retroviral or lentiviral (HIV) backbone. For instance, self-inactivating lentiviral vectors have been developed in preclinical models for ADA-SCID (28), RAG-SCID (29,30), Artemis-SCID (31,32), and agammaglobulinemias (33).…”
Section: Gene Therapy For Scidmentioning
confidence: 99%